2009
DOI: 10.1016/j.vaccine.2009.01.132
|View full text |Cite
|
Sign up to set email alerts
|

A multi-valent vaccinia virus-based tuberculosis vaccine molecularly adjuvanted with interleukin-15 induces robust immune responses in mice

Abstract: Tuberculosis caused by Mycobacterium tuberculosis is responsible for nearly two million deaths every year globally. A single licensed vaccine derived from Mycobacterium bovis, bacille CalmetteGuerin (BCG) administered perinatally as a prophylactic vaccine has been in use for over 80 years and confers substantial protection against childhood tuberculous meningitis and miliary tuberculosis. However, the BCG vaccine is virtually ineffective against the adult pulmonary form of tuberculosis that is pivotal in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…In an earlier report, we described the creation and characterization of a multivalent MVA vectored vaccine which expresses five M. tuberculosis antigens as well as the immunostimulatory cytokine IL-15 (21). We demonstrated that this multivalent MVA vaccine induced robust antituberculosis protective responses and conferred protection against an aerogenic M. tuberculosis challenge.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In an earlier report, we described the creation and characterization of a multivalent MVA vectored vaccine which expresses five M. tuberculosis antigens as well as the immunostimulatory cytokine IL-15 (21). We demonstrated that this multivalent MVA vaccine induced robust antituberculosis protective responses and conferred protection against an aerogenic M. tuberculosis challenge.…”
Section: Resultsmentioning
confidence: 94%
“…MVA recombinant virus expressing ESAT6, Ag85A, Ag85B, HSP65, Mtb39A, and IL-15 was constructed as described previously (21). The E6-85 fusion protein is encoded by the ESAT6 gene fused to the region of the Ag85B gene corresponding to the N terminus without the Ag85B signal sequence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ⌬secA2 gene deletion mutant was isolated by electroporating the pMB179 suicide vector containing a ⌬secA2 allele and a sacB marker into M. tuberculosis H37Rv and then counterselecting on Middlebrook 7H11 plates containing 38 mM (NH 4 ) 2 SO 4 and 3% sucrose (3). The MVA-4TB vaccine was generated by cloning four M. tuberculosis genes (antigen 85A, antigen 85B, ESAT6, and HSP65) as well as the interleukin-15 (IL-15) gene into a modified vaccinia virus Ankara (MVA) vector (27).…”
Section: Methodsmentioning
confidence: 99%
“…It plays critical roles in the activation, proliferation and differentiation of CD8 + T-cells and NK-cells. SC vaccination of mice with a multi-valent TB vaccine with IL-15 induced comparable CD4 + T cell and greater CD8+T cell and antibody responses against Mycobacterium tuberculosis compared with the standard BCG vaccine [342]. Insertion of IL-15 in a recombinant TB virus make it an effective vaccine for generation of consistent anti-TB responses in mice and equal protection as BCG vaccine against M. tuberculosis challenge after heterologous prime/boost regimen (priming with a fusion TB antigen adjuvanted with dimethyldiotacylammonium bromide/monophosphoryl lipid A and boosting with the recombinant TB virus) [343].…”
Section: Interleukinsmentioning
confidence: 96%